Do Managers of U.S. Defined Benefit Pension Plan Sponsors Use Regulatory Freedom Strategically? - KISSER, MICHAEL; KIFF, JOHN; SOTO, MAURICIO (Journal of Accounting Research, 2017)
ABSTRACT We use historical particularities of pension funding law to investigate whether managers of U.S. corporate defined benefit pension plan sponsors strategically use regulatory freedom to lower the reported value of pension liabilities, and hence required cash contributions. For some years, pension plans were required to estimate two liabilities—one with mandated discount rates and mortality assumptions, and another where these could be chosen freely. Using a sample of 11,963 plans, we find that the regulated liability exceeds the unregulated measure by 10% and the difference further increases for underfunded pension plans. Underfunded plans tend to assume substantially higher discount rates and lower life expectancy. The effect persists both in the cross‐section of plans and over time and it serves to reduce cash contributions. We further show that plan sponsor managers use the freed‐up cash for corporate investment and that credit risk is unlikely to explain the finding.